Diurnal and seasonal course of monoterpene emissions from Quercus ilex(L.) under natural conditions application of light and temperature algorithms (Atmospheric Environment, 1997)
Quercus ilex is a common oak species in the Mediterranean vegetation and a strong emitter of monoterpenes. Since the short-term control of monoterpene emissions from this species involved both temperature and light, the usual exponential function of temperature may not be sufficient to model the diurnal and seasonal emission course. In the frame of the BEMA-project (Biogenic Emissions in the Mediterranean Area), we investigated the tree-to-tree, branch-to-branch, diurnal, and seasonal variability of monoterpene emissions from Q. ibex over one and a half years at Castelporziano (Rome, Italy). In addition, w,: checked the suitability of the model developed for isoprene by Guenther et al. (1991, 1993) to simulate the short- and long-term variations of monoterpene emissions from this particular species. We found that the tree-to-tree variability was rather small compared to the experimental error during air sampling and analysis by diverse laboratories. The branch-to-branch variability was noticeable between sun- and shade-adapted branches only. 80% of total emissions were represented by cc-pinene, B-pinene and sabinene, whose proportions were stable over the year and independent of light exposure. The emission factor (emission rate at 30°C and 1000 ~molphotonm-Zs-l ) estimated by the isoprene model or extrapo- lated from measurements was similar: it was about 22 pggdw -r h-r for sun-exposed branches and 2.3 pggdw.-’ h-r for shade-adapted branches. It was rather stable over the seasons except during leaf development. The diurnal and seasonal emission patterns from Q. ibex were simulated in a satisfying way by Guenther’s algorithms especially if we excluded the laboratory variability. For shade-adapted branches, an emission factor 17 times lower had to be applied, but temperature and light responses were unchanged.

EMISSION OF SHORT CHAINED ORGANIC ACIDS , ALDEHYDES AND MONOTERPENES FROM QUERCUS ILEX L . AND PINUS PINEA L . IN RELATION TO PHYSIOLOGICAL ACTIVITIES , CARBON BUDGET AND EMISSION ALGORITHMS (Atmospheric Environment, 1997)
We report on the emission of monoterpenes, short-chained organic acids and aldehydes from Mediterranean oak (Quercus ilex L.) and pine (Pinus pinea L.). All studies were done with dynamic cuvettes enclosing intact branches at the top of the canopy flushed with ambient air. Daily trends are compared with the photosynthetic active radiation (PAR), leaf temperature and the physiological activities of the enclosed branches, i.e. assimilation and transpiration, with special attention on the carbon budget. Oak emits monoterpenes in high amounts, up to 2% of the assimilated carbon. As compared with monoterpenes, short-chained organic acids and aldehydes are of minor importance for oak. However, on a leaf dry-weight basis equal amounts of acids and aldehydes are released from oak and pine. As pine emitted only low amounts of terpenes (below 0.2% of the assimilated carbon) the release of terpenes and oxygenated compounds is of equal importance for this species. A comparison of a modelled light and temperature driven emission with the observed volatile organic compounds (VOC) emissions showed good agreement for monoterpenes as well as for organic acids emitted in the case of oak. For pine only the release of acids showed an adequate relation to the algorithm data, whereas the terpene emissions seemed to be dominated by temperature effects

An overview of the Castelporziano experiments (Atmospheric Environment, 1997)
This paper reviews the major outcomes of the measuring campaigns performed at the Castelporziano nature preserve near Rome, Italy, by 14 European laboratories as part of the BEMA (Biogenic Emissions in the Mediterranean Area)-project. Six campaigns of 1–4 weeks duration were carried out in different seasons of the years 1993–1994 at semi-continuously running test plots in the nature reserve, representing common Mediterranean vegetation types. The aim was to characterise, at the different test plots, the atmospheric chemical and meteorological situations, the plant biomass and physiology, the type, amount and controls of emissions from different plants by means of branch enclosures, and the BVOC emission fluxes from different ecosystems, by scaling up enclosure data from individual sources, and by measuring fluxes directly by use of micrometeorological methods. An important focus during the initial phase of the five year BEMA-project was the harmonisation and improvement of the analytical, physiological and micrometeorological methods used, and the development and testing of new methods for measuring BVOC fluxes.